PERAN PENETAPAN HARGA DAN KUALITAS PELAYANAN DALAM KEPUTUSAN PEMBELIAN KONSUMEN PADA INDOMARET DI KABUPATEN LEBAK - Pipin Suryanisari; Muhamad Thaherudin; Furniawan (The Asia Pacific Journal Of Management Studies, 2026)
Purchasing decisions are important for minimarket business companies/marketers to be able to increase profits and to achieve company goals. Consumer purchasing decisions are influenced by pricing variables and service quality. This research aims to determine the influence of pricing and service quality on purchasing decisions for Indomaret SPBU Cisalam. Respondents in this study were 100 Indomaret customers at the Cisalam gas station The method used by the author is a quantitative method. Sampling using simple random sampling with the slovin formula. Data collection using a survey with a questionnaire was carried out by visiting Indomaret customers in Cisalam gas stations directly. Data were obtained from 100 respondents from 100 questionnaires. The data obtained were analyzed using the SPSS version 20 program. The data analysis technique used to test the hypothesis used the Classical Assumption Formula method, Multiple Linear Regression Analysis, Correlation Correlation, Determination, Simultaneous Regression Coefficient Test (f Test) and Test Partial Regression Coefficient (t Test). From this description, it can be concluded that partially pricing influences purchasing decisions, partially service quality influences purchasing decisions and simultaneously pricing and service quality influence purchasing decisions at Indomaret SPBU Cisalam